Novel sulfonamide incorporating piperazine, aminoalcohol and 1,3,5-triazine structural motifs with carbonic anhydrase I, II and IX inhibitory action - Havránková, Eva; Csöllei, Jozef; Vullo, Daniela; Garaj, Vladimír; Pazdera, Pavel; Supuran, Claudiu T (Bioorganic chemistry, 2018)
A new series of s-triazine derivatives incorporating sulfanilamide, homosulfanilamide, 4-aminoethyl-benzenesulfonamide and piperazine or aminoalcohol structural motifs is reported. Molecular docking was exploited to select compounds from virtual combinatorial library for synthesis and subsequent biological evaluation. The compounds were prepared by using step by step nucleophilic substitution of chlorine atoms from cyanuric chloride (2,4,6-trichloro-1,3,5-triazine). The compounds were tested as inhibitors of physiologically relevant carbonic anhydrase (CA, EC 4.2.1.1) isoforms. Specifically, against the cytosolic hCA I, II and tumor-associated hCA IX. These compounds show appreciable inhibition. hCA I was inhibited with KIs in the range of 8.5-2679.1 nM, hCA II with KIs in the range of 4.8-380.5 nM and hCA IX with KIs in the range of 0.4-307.7 nM. As other similar derivatives, some of the compounds showed good or excellent selectivity ratios for inhibiting hCA IX over hCA II, of 3.5-18.5. 4-[({4-Chloro-6-[(4-hydroxyphenyl)amino]-1,3,5-triazin-2-yl}amino)methyl] benzene sulfonamide demonstrated subnanomolar affinity for hCA IX (0.4 nM) and selectivity (18.50) over the cytosolic isoforms. This series of compounds may be of interest for the development of new, unconventional anticancer drugs targeting hypoxia-induced CA isoforms such as CA IX.
Keywords: inhibitory karboanhydras; Humans; Carbonic Anhydrase I; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Carbonic Anhydrase IX; Amino Alcohols; Dose-Response Relationship, Drug; Triazines; sulfonamidy; Carbonic Anhydrase II; Piperazine; piperazin; karboanhydrasa II; karboanhydrasa IX; lidé; Carbonic anhydrase; Antigens, Neoplasm; molekulární struktura; Molecular Structure; antigeny nádorové; triaziny; 1,3,5-Triazine; Carbonic Anhydrase Inhibitors; vztah mezi dávkou a účinkem léčiva; Enzyme inhibition; karboanhydrasa I; Benzene sulfonamides; aminoalkoholy; Isoform selectivity; Sulfonamides